Determinants of ADL and IADL disability in older adults in southeastern Poland - Ćwirlej-Sozańska, Agnieszka; Wiśniowska-Szurlej, Agnieszka; Wilmowska-Pietruszyńska, Anna; Sozański, Bernard (My University, 2019)
Background: The extension of the life span has led to an increase in the number of older people and an increase in the prevalence of disability in people over 60 years of age. The aim of this study was to assess the prevalence of ADL and IADL disability and to analyze its determinants among people aged 60 and older living in southeastern Poland. Methods: This cross-sectional study was carried out among a randomly selected, representative population of people aged 60 and older living in southeastern Poland. Disability was assessed using the Katz Index of Independence in Basic Activities of Daily Living and Instrumental Activities of Daily Living. Logistic regression models were used to identify the factors related to ADLs and IADLs. For the variables that were included in the above models, their clustered influence on the increase in the odds ratio for the occurrence of an ADL or IADL limitation was also examined. Results: The research results show that 35.75% of the participants reported at least one problem with IADLs. At least one problem with ADLs was reported by 17.13% of the participants. The most significant modifiable factors influencing the occurrence of disability were the presence of barriers in the participant’s environment, poor relations with relatives, a lack of social contacts, multimorbidity and pain. A multiple increase in the odds ratio of disability was found with the presence of pairs of analyzed factors. The highest odds ratio of at least one ADL limitation was observed for the combination of barriers in the participant’s environment with multimorbidity (OR 74.07). With regard to IADL disability, the highest odds ratio was observed for the combination of pain on the VAS scale ≥ 3 points with older age (OR 19.47). Conclusions: The study showed a high prevalence of ADL and IADL disability in older people living in southeastern Poland. It also indicated the extent to which modifiable factors influenced the occurrence of disability and the extent to which the risk of disability increased with the presence of pairs of factors, especially those that included environmental barriers in the participant’s environment.
Keywords: aged, disability, factors, basic activities of daily living, instrumental activities of daily living